О построении матричнозначной функции Ляпунова для линейной системы с квазипериодическими коэффициентами - Лила, Д.М.; Слынько, В.И. (Видавничий дім "Академперіодика" НАН України, 2007)
One of the ways of constructing Lyapunov’s matrix-valued function for a linear system of a differential equations with quasiperiodic coeficients has been proposed. On the basis of this function, the conditions for asymptotic stability of a class of linear systems are obtained. This allows one to investigate the systems with unstable independent subsystems.